An integrated olive stone biorefinery based on a two-step fractionation strategy - Padilla-Rascón, Carmen (2022)
ABSTRACT: Olive stones (OS) constitute a waste lignocellulosic material produced by the olive oil industry in great amounts, that currently is only used as a low-value energy source for industrial or domestic boilers. Having in view its full valorization, this work proposes and validates an integrated strategy aiming to obtain three different streams of sugars / lignin-derived compounds. Dilute acid hydrolysis was used to obtain a xylose-rich hydroysate that was chemically converted into furfural with a 48.7 % yield. The resulting acid-pretreated solid biomass that consisted mainly of lignin and cellulose, was subjected to a catalyzed ethanol-based organosolv delignification. Temperature, time, and sulphuric acid concentration were optimized in order to recover added-value lignin products and digestible cellulose. At the optimal conditions (190 degrees C and 30 min), a 50 % delignification was reached, together with the highest enzymatic hydrolysis yields (190 g glucose/kg of OS). Phenolic compounds content in organosolv liquors reached 41.6 mg GAE/g OS. This extract presented an antioxidant capacity up to 10.9 mg TE/g OS. The pretreated solid fraction was used as a substrate for ethanol production by a pre-saccharification and simultaneous saccharification and fermentation process, enabling to obtain an ethanol concentration of 47 g/L, with a fermentation yield of 61.4 % of the theoretical maximum. Globally, from 100 kg of OS processed according to this experimental scheme, 6.9 kg of furfural, 6.2 kg of ethanol, 7.4 kg of lignin, and 4.2 kg of phenolics compounds can be obtained as main products, thus constituting a way of valorization of renewable material in a multiproduct biorefinery strategy.